1998
DOI: 10.1179/mst.1998.14.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cooling rate and MnS inclusions on hot ductility of steels

Abstract: The influence of cooling rate on the hot ductility of plain C-Mn steels containing 0'1-0'7%C has been examinedfor tensile specimens tested in the temperature range 1000-550°C. Increasing the cooling rate from 10 to 60 K min -1 in all cases caused the ductility to deteriorate. This deterioration was found to be associated with the presence of a finer sulphide distribution in the ferrite surrounding the austenite grains, as well as a reduction in the thickness of the ferrite covering. Decreasing the strain rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…This has become particularly important with the advent of thin slab casting, where cooling rates are much higher than in conventional continuously cast steel. Generally, the average cooling rate from the mould to the straightening temperature are 60~100 o C/min for conventional casting (220 to 250mm thick slab) and It is found that increasing the cooling rate to the test temperature after solution treatment results in deeper troughs Fig.2.20 [75]. This has been shown to be related to a finer sulphide re-precipitation at the γ grain boundaries produced by the higher cooling rate so that again the spacing between the particles is reduced making it easier for ductile cracks to link up and give failure [75].…”
Section: Cooling Ratementioning
confidence: 99%
See 3 more Smart Citations
“…This has become particularly important with the advent of thin slab casting, where cooling rates are much higher than in conventional continuously cast steel. Generally, the average cooling rate from the mould to the straightening temperature are 60~100 o C/min for conventional casting (220 to 250mm thick slab) and It is found that increasing the cooling rate to the test temperature after solution treatment results in deeper troughs Fig.2.20 [75]. This has been shown to be related to a finer sulphide re-precipitation at the γ grain boundaries produced by the higher cooling rate so that again the spacing between the particles is reduced making it easier for ductile cracks to link up and give failure [75].…”
Section: Cooling Ratementioning
confidence: 99%
“…This has been shown to be related to a finer sulphide re-precipitation at the γ grain boundaries produced by the higher cooling rate so that again the spacing between the particles is reduced making it easier for ductile cracks to link up and give failure [75]. It should be appreciated that for a given inclusion volume fraction, although finer inclusions will generally increase the energy required for ductile fracture at room temperature because they are less deformable, this does not apply to the present situation where the failures are intergranular and the linking up of the cavities is more important than their ease of formation [75].…”
Section: Cooling Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Increasing the Mn content in the steel will increase the probability of the combination of sulfur and manganese, and the formula (1) in the equilibrium forward movement, which can hinder the formation of FeS and other low melting point compounds in the austenite grain boundaries. theoretically to achieve this goal, manganese sulfur ratio to reach 7 [3][4][5].…”
Section: Experimental Methods and Analysismentioning
confidence: 99%